Effect of extended embryo culture after thawing on clinical pregnancy rate - Sh. Gaafar; T. Hanafy; S. El Morshedy; H. Mansour (IMR Press, 2020)
Purpose: This randomized controlled trial is aiming to compare the clinical pregnancy rate of immediate versus delayed post thawing embryo transfer in frozen embryo transfer (FET) cycles. Materials and Methods: The study was conducted on 150 FET cycles in which embryos were vitrified on day 2 or 3. After thawing, cases with more than 50% blastomere loss were excluded as well as cases with recurrent implantation. The endometrium was prepared by programmed estrogen/progesterone method. After thawing, cases were randomized to immediate embryo transfer or extended culture for 18-72 hours before transfer. Results: Number of cryopreserved embryos and survival rates were similar in both groups. Survival rates was above 95% in both groups and in the extended culture group 72.1% of embryos resumed miosis. Clinical pregnancy rate was 50.7% in immediate transfer group and 41.3% in the extended culture group. Conclusion: Extended culture after thawing helps in embryo selection but does not increase clinical pregnancy rate.